Evaluating vertical transmission of sexually transmitted infections to newborns - Dinamene Oliveira; João Piedade; Rita Castro; Ângela Lopes; Maria do Rosário Martins; Filomena Pereira (Journal of Infection in Developing Countries)
Introduction: Sexually transmitted infections are among the most frequent infections affecting pregnant women. We assessed the transmission of hepatitis B virus, human immunodeficiency virus type 1 and Treponema pallidum to newborns from infected parturients.